MARKERS OF LOW-GRADE INFLAMMATION IN PATIENTS WITH ACUTE CORONARY SYNDROME AND 2 TYPE DIABETES MELLITUS - Bondareva, O. O.; Fedorov, S. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
Cardiovascular diseases cause approximately one-third of all deaths in the world, of which 7.5 million deaths are estimated to be due to ischemic heart disease (IHD). Acute coronary syndromes (ACS) and sudden death cause most IHD-related deaths, which represent 1.8 million deaths per year. Established, that patients with diabetes mellitus (DM) are more likely to experience of ACS and heart failure and are at greater risk for dying after an acute cardiac event, than patients without diabetes. The purpose of this study is evaluation of leukocyte and its populations count, leukocytes indices and plasma level of high sensitive C-reactive protein (hsCPR) in patients hospitalized due to ACS with or without of 2 type DM. Material and Methods. We observed of 124 patients with ACS which were randomized into two groups: 1st group – 93 patients with ACS and DM; 2nd group – 31 patients with ACS without 2 type DM. 30 apparently healthy persons were included into control group. We studied of leukocytes count and their subpopulations in blood; calculated of their subpopulation indices: neutrophils to lymphocytes ratio (NLR), neutrophils to monocytes ratio (NMR), neutrophils to lymphocytes+monocytes ratio (N/LMR), lymphocytes to monocytes ratio (NMR) at admission. The plasma levels of hs-CRP were detected by ELISA method. Results of study. The significant increase of white blood cells count and neutrophils count in patients with ACS at admission was detected in our study, especially in cases with DM. On the contrary, the counts of lymphocytes were decreased in patients with ACS and ACS with 2 type DM, versus data in control group. In patient with ACS the increased parameter of NMR was observed (p<0.001). Similarly, the following indices were higher, compared with control group parameters: NLR – for 3.32 times (in patients with ACS and DM) and for 2.43 times (in patients with ACS and without DM) (p<0.001); N/LMR – for 2.98 times (in patients with ACS and DM) and for 2.14 times (in patients with ACS and without DM) (p<0.001). On the contrary, LMR was decreased in both groups of patients with ACS – for 1.4 times and 1.36 times, respectively (p<0.05). The increased plasma levels of hs-CRP were detected in patients with ACS, more significant – in case of 2 type DM (fig. 1): for 2.1 times and for 2.59 times, respectively (p<0.001). Conclusion. ACS is characterized of raised white blood cells and neutrophils count and low lymphocyte count, especially in cases of association with 2 type Diabetes Mellitus. Low-grade inflammation in patients with ACS and DM caused of increased levels of hs-CRP and some leukocyte ratios: NMR, N/LMR, NLR.